Comfort Theory Dari Katharine Kolcaba: Tinjauan Filosofis dan Aplikatif Dalam Praktik Keperawatan Modern - Purwanti, Eni; Damanik, Siti Rahmalia (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Nursing care that focuses on improving quality of life needs a holistic and human-centered approach. One theory that supports this is the Comfort Theory by Katharine Kolcaba, which puts comfort at the heart of nursing, covering physical, psycho-spiritual, social, and environmental aspects. This literature review aims to explore the philosophy, practical use, and effects of applying Comfort Theory in different nursing settings. The literature was collected from PubMed, ScienceDirect, and Google Scholar, covering publications from 2015 to 2024, including research articles, books, and policy documents. The results show that using Comfort Theory helps nurses provide patient-centered care, such as playing music after surgery, offering spiritual counseling for terminal patients, peer support for those with chronic illnesses, and making hospital rooms more comfortable. Some challenges include limited time for nurses, cultural differences, and lack of training. However, strong leadership, supportive hospital policies, and regular training can help overcome these issues. Data from several studies show that applying this theory improves patient satisfaction, shortens hospital stays, and reduces anxiety. In conclusion, Comfort Theory is very useful in today’s nursing practice to help improve the quality of life of patients through care that focuses on overall comfort. Keywords: Comfort Theory, Nursing Philosophy, Holistic Nursing, Nursing Interventions,, Quality of Life.